2016
DOI: 10.4028/www.scientific.net/msf.879.2377
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and Fatigue Properties of Miniature Size Specimens of Sn-5Sb Lead-Free Solder

Abstract: Tensile and low cycle fatigue properties of Sn-5Sb (mass%) solder were investigated with miniature size tensile specimens. The effect of temperature and strain rate on tensile properties and the effect of temperature on low cycle fatigue properties were examined. Tensile strength increases with increasing strain rate regardless of temperature investigated. For elongation, the effect of temperature on it is negligible although it slightly increases with increasing strain rate. The low cycle fatigue life of Sn-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…For the solder alloy used in this product, a combination of high heat durability, good tensile properties and high fatigue resistance is required. 8,9) SnSb alloys, which are lead-free high-temperature solders, are possible alternatives to Pb-rich solders. It has been reported that Sn5Sb (mass%) has good electric resistivity, high fracture strength and excellent fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the solder alloy used in this product, a combination of high heat durability, good tensile properties and high fatigue resistance is required. 8,9) SnSb alloys, which are lead-free high-temperature solders, are possible alternatives to Pb-rich solders. It has been reported that Sn5Sb (mass%) has good electric resistivity, high fracture strength and excellent fatigue resistance.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Sn5Sb (mass%) has good electric resistivity, high fracture strength and excellent fatigue resistance. 9,10) It has also been reported that the addition of microelements has the potential to enhance the mechanical properties of Sn-based solders. Many researchers have studied the effects of Au, Ag or Cu in SnSb solder on various properties.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it is essential for the practical use of the power electronics devices using the power semiconductors that power module components be withstood high heat environment. In particular, a die-attach material used between the power semiconductors and an insulated substrate such as Al 2 O 3 and AlN requires both good tensile properties and high fatigue resistance [6,7]. In the present, Pb-rich solder alloys which is over 85 mass% Pb for high temperature environment are mainly used as the die-attach material despite Pb being toxic [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the Sn-Sb solder alloys which have highest melting temperature range among existing lead-free solder alloys, are able to replace the Pb-rich solder alloys [7][8][9][10][11][12][13][14]. It has been reported that the Sn-Sb solder alloys have low electric resistivity and good mechanical properties [7,15]. However, in order to apply the Sn-Sb to the next-generation power semiconductors, it is necessary to further improve the tensile and fatigue properties in high temperature environment.…”
Section: Introductionmentioning
confidence: 99%
“…Sn-Sb alloys are one of the candidates for the substitution of the Pb-rich solders [9][10][11]. It has been reported that Sn-5Sb (mass%) has excellent thermal fatigue behaviors and relatively high fracture strength [12,13]. In addition, in Sn-Sb alloys with high concentration of Sb, mechanical strength is improved by solid-solution of Sb in β-Sn matrix and dispersion of SbSn compounds [14].…”
Section: Introductionmentioning
confidence: 99%